Stealing democracy the new politics of voter suppression. - Overton, Spencer (W.W. Norton, 2006)
Politicians spew shallow sound bites that describe a "free" American people who govern themselves by selecting their representatives. In reality, politicians from both parties maintain power by selecting specific voters. Elected officials and bureaucrats control thousands of election practices that determine political winners and losers, including the location of election district boundaries, the number of voting booths at urban polling places, and English-only ballots. Spencer Overton, a professor at George Washington University Law School, uses real-life stories to show how these seemingly insignificant practices channel political influence and determine policies on war, schools, clean air, and many other issues that shape our lives. He also exposes the pressure points in this Orwellian system and provides strategies toward restoring government by the people, such as removing redistricting power from self-interested partisans and renewing parts of the Voting Rights Act. Overton's compelling case is vital to the future of our democracy."--BOOK JACKET